Structural and Psychometric Properties of Neck Pain Questionnaires Through Patient-Reported Outcome Measures: A Systematic Review - Manuel Gonzalez-Sanchez; Álvaro Jesús Reina-Ruiz; Guadalupe Molina-Torres; Sandra Kamila Trzcińska; Elio Carrasco-Vega; Alena Lochmannová; Alejandro Galán-Mercant (Medicina, 2025)
Background and Objectives: Questionnaires are patient-reported outcome measures that require a validation process to assess their reliability and replicability. Over time, questionnaires have not only focused on a single health condition, such as neck pain, but also expanded their assessment spectrum to other areas in order to gather additional and relevant information from the patient. The main objective of this study was to conduct a systematic review of the different structural and psychometric characteristics of neck pain questionnaires. Materials and Methods: A systematic review was conducted following the PRISMA recommendations. The search strategy was implemented across various databases (PubMed, Cochrane, EMBASE, CINHAL, Trip Medical Database, Scopus) using terms such as neck pain, cervicalgia, cervical pain, questionnaire, survey, index, validity, validation, and reliability. COSMIN criteria were used to identify valid questionnaires for this systematic review based on their psychometric properties. Results: A total of 15 articles were identified in this systematic review, of which 8 assessed the level of disability, while the rest evaluated dizziness in neck pain, anxiety and/or depression, beliefs about fear and avoidance, and perception of scarring and symptoms after neck surgery. The main findings show that neck pain questionnaires exhibit very good values for reliability and internal consistency, along with a high variability for construct validity. Conclusions: This study highlights the good values exhibited by neck pain questionnaires despite their heterogeneity in structural characteristics, demonstrating good values in psychometric properties. Nevertheless, the latter should be further investigated to gather more information.